Is Fiduciary Deed Suitable for Aircraft in Indonesia? - Y. , Annalisa; Zaidan, Murzal; M. , Syaifuddin; Febrian,; Nurhidayatuloh,; Elmadiantini, (International Journal of Psychosocial Rehabilitation, 2020)
This article explores the imprecise notary legal reasons for making an aircraft fiduciary deed when it is based on the principles of applicable law and the concept of collateral law. This examines also the legal protection of the creditor as the recipient of the guarantee when the debtor fails to fulfill his/her duty. It is normative legal research trying to find the basic rules of collateral law, fair values, the validity of the rule of law, and legal norms. It uses historical and comparative approaches. The result shows that it is imprecise if the notary makes an aircraft fiduciary deed in an aircraft financing loan agreement. The reasons are, firstly, the fiduciary law explicitly states that the guarantee of an aircraft is in the form of a mortgage. Secondly, an aircraft is a registered object, which is analogous to an immovable object. For these reasons, it is more precise to use a collateral figure in the form of a mortgage deed as applied to a ship in shipping law.